Proximate, Total Phenolic, Antioxidant Activity and Amino Acids Profile of Bali Indigenous Chicken, Spent Laying Hen and Broiler Breast Fillet - Okarini , Ida Ayu; Purnomo, Hari; Aulanni`am; Radiati, Liliek Eka (International Journal of Poultry Science, 2013)
Fresh chicken breast fillet of Bali indigenous chicken, spent laying hen and broiler were studied for proximate, total phenolic, antioxidant activity and its amino acids profile. Broiler breast fillet contained higher moisture, fat, and ash contents (P<0.05) compared to Bali indigenous chicken as well as spent hen breast fillets, but protein content, total phenolic content and DPPH radical scavenging activity were lower (P<0.05). The amino acids profile of broiler showed that only methionine contents were higher (P<0.05) compared to the other chicken breast fillet samples. Whilst Bali indigenous chicken had highest (P<0.05) glutamic acid and arginine compared to the other chicken meat, and essential amino acid like valine, phenylalanine, threonine, leucine and lysine contents of Bali indigenous chicken was no differ (P>0.05) with spent laying hen, and had higher (P<0.05) compared to broiler breast fillet.